From Hybrid Organizations to Social-purpose Hierarchies: Toward a Transaction Cost Economics of Social Enterprises. (July 2020) - Agafonow, Alejandro
Building on Oliver E. Williamson's work, this article lays the basis for a transaction cost theory of social enterprises. It is submitted that the more proprietary-centred the creation of value is, the lower the governance costs of economizing on bounded rationality to protect patrons from the hazard of opportunism. Since not all productive activities can be organized within the range of the lowest governance costs, a discrete structural analysis is developed, with different ranges of governance costs suitable for different purposes depending on the kinds of value creation intended and the class of patrons to be protected. Accepting higher governance costs is justified by preventing the exploitation of bargaining asymmetries at the expense of selected classes of patrons like disadvantaged customers and stakeholders at large, subject to what is feasible, or Williamson's remediableness standard . JEL: D23, M14